Examining the intended usage behaviour of consumers when accessing and using smart devices - Maly, Phil (2021)
In 2020, more than two third of the world’s population are using mobile phones or other internet devices. Researchers already found out that there are differences in the user’s motivation to use different internet devices, and numerous studies are conducted about the technology adoption of new devices. However, there is only little research about the motivations of users to continue to use a certain device and in which context a device is preferably used. This is highly important for marketers and managers to better under-stand the usage behaviour of costumers and users to improve all online marketing ef-forts. Therefore, this study examines technological, psychological, and behavioural drivers of users’ intention to continue to use mobile phones and personal computers, which are the two most used connected devices worldwide. More specifically, the effect of perceived ubiquity on continuance intention is explored, which is a relatively new concept and refers to technologies, which are available anytime and everywhere. Addi-tionally, the effect of habit as a behavioural driver as well as perceived self-efficacy, per-ceived enjoyment and personal innovativeness as psychological drivers were included into the research. The study is conducted with a quantitative approach. The data is col-lected with the help of an online survey (N=121), which was distributed to participants of different countries. The collected information is analysed by partial least square structural equitation modelling (PLS-SEM). Based on this study, perceived enjoyment is the only driver which affects the continuance intention to use both, a personal computer and a mobile phone. Also, the relatively new concept of perceived ubiquity is the most relevant factor for the continued use of mobile phones, while habit is the strongest pre-dictor of the continuance intention of personal computers. All the other antecedents of continuance intention were found to have no significant effect whether on the continued intention to use personal computers nor on the continued intention to use mobile phones.